Theory of mind and loneliness: Effects of a conversation‐based training at school. (4th August 2020) - Caputi, Marcella; Cugnata, Federica; Brombin, Chiara
Abstract : Conversation‐based training programmes are known to be effective in enhancing theory of mind (ToM). The possible consequences of such training programmes on the understanding of other constructs have rarely been investigated. The present research aimed to evaluate the effects of two different types of conversation‐based training on ToM and loneliness. Two hundred and ten fourth and fifth graders (52% boys; Mage = 9.66 years, SD = 0.85), randomly divided into two groups (ToM and no‐ToM training condition), were administered at a 5‐week intervention. ToM and loneliness were measured before and twice after the intervention (1 week and 2 months later). Linear mixed‐effects models showed that, soon after the intervention, children in the ToM training condition obtained significantly higher ToM scores and significantly lower loneliness scores compared to children in the no‐ToM training condition. Nonetheless, at the follow‐up, ToM and loneliness scores were not significantly different for the two training conditions. These findings suggest that a relatively short intervention based on group discussion of mental states is sufficient to improve mentalizing abilities and to tackle feelings of loneliness among fourth and fifth graders in the short but not in the long term.